2005
DOI: 10.1111/j.1439-0531.2005.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Computer‐Assisted, Morphometric‐Derived Sperm Characteristics Reflect DNA Status in Canine Spermatozoa?

Abstract: It is widely accepted that sperm morphology is a strong indicator of semen quality. As the sperm head mainly comprises the sperm DNA, it is have been proposed that subtle changes in sperm morphology may be related to abnormal DNA content. Semen from four mongrel dogs was used to investigate DNA quality by means of the sperm chromatin structure assay (SCSA), and for computerized sperm morphometry (CASMA). Each sperm head was measured for nine primary parameters [head area (A), head perimeter (P), head length (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 19 publications
5
49
2
Order By: Relevance
“…Further, any subtle changes in sperm chromatin condensation or alteration in sperm histone-protamine ratio necessary for chromatin packing may directly reflect in changes in head morphology and morphometry [10]. Experimental studies have demonstrated a positive correlation between abnormal sperm head morphology and DNA damage and chromatin integrity, but such relationship in infertile patients was not extensively studied [11][12][13]. To our knowledge, this is one of the few studies which compared and analyzed retrospectively, the correlation of sperm head morphology parameters assessed by CASA with DNA fragmentation analysis and chromatin integrity in infertile patients.…”
Section: Introductionmentioning
confidence: 99%
“…Further, any subtle changes in sperm chromatin condensation or alteration in sperm histone-protamine ratio necessary for chromatin packing may directly reflect in changes in head morphology and morphometry [10]. Experimental studies have demonstrated a positive correlation between abnormal sperm head morphology and DNA damage and chromatin integrity, but such relationship in infertile patients was not extensively studied [11][12][13]. To our knowledge, this is one of the few studies which compared and analyzed retrospectively, the correlation of sperm head morphology parameters assessed by CASA with DNA fragmentation analysis and chromatin integrity in infertile patients.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing interest and attempts for improvement in semen cryobiology of canines in last five years (Yu et al, 2002;Núñez-Martínez et al, 2005Neagu et al, 2010) have led to well-established cryoprotective protocols allowing better whelping rates (over 70%) (Thomassen et al, 2006) and artificial insemination (AI) of bitches with frozen-thawed semen is now being offered as a routine clinical service by many veterinarians world-wide (Yu et al, 2002).…”
mentioning
confidence: 99%
“…Perez-Llano et al (2006) [18] found that sperm extenders delay, or partially prevent, sperm DNA fragmentation in boar spermatozoa. A strong correlation between the sperm chromatin structure assay (SCSA) and sperm head morphometry in dog spermatozoa has been found [19], but so far, only one study has been published on DNA fragmentation of dog semen [20]. Epididymal sperm and ejaculated semen from Iberian deer, dogs, and rams was collected, diluted with Tris Sodium Chloride Ethylene-diamine-tetra-acetic Acid (TNE) buffer and preserved in LN 2 in an ultra cold freezer (-80ºC).…”
Section: Introductionmentioning
confidence: 99%
“…Results were analyzed using least square means (LSMs). Period 1 included days 1-8; period 2 included days 9-14; and period 3 included days [15][16][17][18][19][20][21][22][23]. Different superscript letters (a-c) indicate differences (P<0.05) among the extenders.…”
Section: Motilitymentioning
confidence: 99%
See 1 more Smart Citation